2006
DOI: 10.1128/mcb.26.10.3917-3934.2006
|View full text |Cite
|
Sign up to set email alerts
|

Furin-, ADAM 10-, and γ-Secretase-Mediated Cleavage of a Receptor Tyrosine Phosphatase and Regulation of β-Catenin's Transcriptional Activity

Abstract: Several receptor protein tyrosine phosphatases (RPTPs) are cell adhesion molecules involved in homophilic interactions, suggesting that RPTP outside-in signaling is coupled to cell contact formation. However, little is known about the mechanisms by which cell density regulates RPTP function. We show that the MAM family prototype RPTP is cleaved by three proteases: furin, ADAM 10, and ␥-secretase. Cell density promotes ADAM 10-mediated cleavage and shedding of RPTP. This is followed by ␥-secretase-dependent int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
110
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(116 citation statements)
references
References 51 publications
3
110
0
2
Order By: Relevance
“…This event is followed by γ-secretase-dependent cleavage of the remaining transmembrane part of RPTP-κ to release the catalytic phosphatase intracellular (PIC) fragment from the membrane, thereby allowing its nuclear translocation. PIC of RPTP-κ is an active PTP that binds to and dephosphorylates its substrate β-catenin in the nucleus, which enhances transcriptional activity of β-catenin (Anders et al 2006).…”
Section: Rptp-κ and The R2b Subfamilymentioning
confidence: 99%
“…This event is followed by γ-secretase-dependent cleavage of the remaining transmembrane part of RPTP-κ to release the catalytic phosphatase intracellular (PIC) fragment from the membrane, thereby allowing its nuclear translocation. PIC of RPTP-κ is an active PTP that binds to and dephosphorylates its substrate β-catenin in the nucleus, which enhances transcriptional activity of β-catenin (Anders et al 2006).…”
Section: Rptp-κ and The R2b Subfamilymentioning
confidence: 99%
“…Inhibition of PTP activity by pervanadate treatment disrupts epithelial junctions and, interestingly, impairs E-cadherin-activated Src signaling . Although some studies have reported a role for cell-contact-associated PTPs in controlling the integrity and function of epithelial junctions (Anders et al, 2006;Espejo et al, 2010;Fuchs et al, 1996;Müller et al, 1999;Sheth et al, 2007), none of the identified PTPs has been shown to control junctional SFKs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Maretzky et al reported that ADAM10 modulated the nuclear translocation of β-catenin through shedding of cadherin E, resulting in enhanced expression of cyclin D1 and c-Myc, thus leading to the promotion of proliferation (29). Furthermore, ADAM10 contribution to cell proliferation by increasing the transcriptional activity of β-catenin involves the action of receptor protein tyrosine phosphatases (30). In the present study, the expression and clinicopathological significance of ADAM10 in laryngeal Table III.…”
Section: Discussionmentioning
confidence: 77%